Deleção oócito-específica da Rad51 em murinos e seu impacto sobre a função mitocondrial e a fertilidade - Augusto Neto, José Djaci (Universidade Federal de São Carlos, 2020)
One of the first signs of aging in humans is the decrease in female fertility, which is accompanied by a reduction in the expression of proteins that integrate the Double Strand Break (DSB) repair machinery, such as BRCA1, ATM, MRE11 and RAD51. Therefore, the deficiency of such proteins may result in oocytes of poor quality, with early separation of sister chromatids, aneuploidy, chromosomal breaks as well as increased apoptosis susceptibility. Hence, the present work aimed at inducing oocyte-specific deletion of Rad51 in mice and assess its effects upon fertility, gamete development and mitochondria function. As a result, wild-type (Rad51fl/fl) and knockout (Rad51 +/- , Rad51-/- ) females delivered, respectively 8.8, 7.8 and 2.8 pups/litter. Moreover, pups born to Rad51-/- oocytes showed a ~30% mortality rate; however the pups that survived until weaning were considered viable. It was not observed an effect of knockouts on oocyte growth, cumulus-oocyte complex morphology, and the number of ovulated oocytes with first polar body. Likewise, Rad51 knockout did not impact on mitochondrial function as judged by assessing the levels of NAD(P)H, FAD, mitochondrial membrane potential and ATP. However, Rad51-/- oocytes presented a larger level of reactive oxygen species. Therefore, we conclude that RAD51 is not essential for oocyte development and mitochondrial function, however its deficiency results in subfertility.
Oocyte-specific deletion of Rad51 in mice and its impact on mitochondrial function and fertility
Keywords: Foliculogênese; Oócito; Mitocôndria; Subfertilidade; RAD51; Oocyte; Mitochondria; Subfertility; CIENCIAS BIOLOGICAS::GENETICA